Determination of Limiting Heat Flux for The Inception of Nucleate Boiling Regime for Crude Oils - Rehman, O.U. (Penerbit Akademia Baru, 2021)
Finding the limiting heat flux above which nucleate boiling starts and below which forced convective heat transfer exists is a crucial task for the accuracy of results from crude oil fouling tests. In this study, crude oils from two sources were tested at bulk temperatures of 100, 120 and 140 Â°C and different velocities. Heat transfer coefficient increased gradually with bulk temperature indicated lowering of the viscosity at high temperatures which promoted turbulence and enhanced heat transfer. The velocity effects were similar to that of bulk temperatures on maximum heat transfer coefficient while less heat flux was required to achieve the same surface temperature at lower velocities. Deshannavar and Ramasamy's model to predict maximum heat flux was compared with experimental results and a poor estimation was observed for the crude oils tested. Â© 2021. All Rights Reserved.